PARTISIPASI MASYARAKAT PESISIR DALAM PENGELOLAAN KAWASAN MANGROVE DI TELUK KOTANIA - Hellen Nanlohy (Universitas Gadjah Mada, 2014)
Kotania bay is one of the bay sin the district of West Seram, Maluku Province which has a value of mangrove area swith high economi cutilization. Utilization of mangrove areas should be managed well by involving the public directly in the coastal zone management program. This study aims to analyze the level of participation of coastal communities in the Kotania bay in the management of mangrove areas to stay awake and sustainable. The purpose of this study is to analyze the level of community participation in the management of mangrove areas in the Kotania bay. The research design was a descriptive survey research and uses analysis of the span of a score. Data a collected by gathering primary data and secondary data. The primary data obtained from interviews with respondents who directly serve asactorsin the use of mangrove areas for livelihood. Data were analyzed using analysis of the level of participation by using a range of scales. The analysis showed that 30.7% of the public strongly supports the management of coastal mangrove areas or extremely participate in mangrove area management activities, 65.3% supports or participates in the management of mangrove areas and a small portion which 4.0% were hesitant to participate in the mangrove area management activities.